Field Application of Organic Fertilizers Triggers N2O Emissions From the Soil N Pool as Indicated by 15N-Labeled Digestates - Häfner, Franziska; Ruser, Reiner; Claß-Mahler, Ingrid; Möller, Kurt (Frontiers in Sustainable Food Systems, 2021)
Anaerobic digestion (AD) can generate biogas while simultaneously producing digestate which can be used as fertilizer. Feedstocks used for AD influence digestate composition, which in turn may affect carbon (C) and nitrogen (N) turn-over in soils and subsequently influence nitrous oxide (N2O) emissions after soil application. Assessment of greenhouse gas emissions from digestates can help to evaluate the overall sustainability of an agricultural production system. The objective of this study was therefore to evaluate and understand the effect of differences in digestate composition on in situ N2O emissions within the 1st weeks after application of seven digestates. The digestates were derived from different feedstocks and 15N-labeled, either in total N or only in ammonium-N. Therefore, the experimental design enabled us to differentiate between potential N2O-N sources (i.e., digestate N or soil N). Furthermore, it allowed to distinguish to some extent between organic-N and ammonium-N as potential N sources for denitrification. Digestates were homogeneously incorporated into the upper 5 cm of microplots in an arable Haplic Luvisol in South Germany at a rate of 170 kg N ha−1. After application, N2O fluxes were measured for ~60 days (May-July) using the closed chamber method in 2 experimental years. Mainly due to higher precipitations in the 1st year, cumulative N2O emissions were higher (312–1,580 g N2O-N ha−1) compared to the emissions (133–690 g N2O-N ha−1) in the 2nd year. Between 16–33% (1st year) and 17–38% (2nd year) of N2O emissions originated from digestate N, indicating that digestate application triggered N2O production and release mainly from soil N. This effect was strongest immediately after digestate application. It was concluded that the first (short term) peak in N2O emissions after digestate application is largely related to denitrification of soil-N. However, the experimental setup does not allow to differentiate between the different denitrification pathways. Weather conditions showed a substantial effect on N2O emissions, where the correlation between N2O and CO2 flux rates hinted on denitrification as main N2O source. The effect of digestate composition, particularly organic N from the digestate, on soil N2O emissions seems to be of minor relevance.